2016
DOI: 10.1136/bcr-2015-213940
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial anthracofibrosis with interstitial lung disease: an association yet to be highlighted

Abstract: Bronchial anthracofibrosis (BAF), an emerging pulmonary disease due to long-standing exposure to biomass fuel smoke, is predominantly seen in females from developing nations. BAF is known to be associated with tuberculosis, pneumonia, chronic obstructive pulmonary disease and lung cancer, but the association of BAF with interstitial lung disease (ILD) is rare and yet to be highlighted. A 72-year-old woman with a 30-year history of exposure to biomass fuel smoke presented with dry cough and exertional dyspnoea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Of the 58 patients with isolated BAF from Iran [17], peribronchial soft tissue thickening, bronchial narrowing or obstruction, segmental atelectasis, and lobar or multilobar collapse were the major findings. The CT findings in the two patients reported from India [7,14] included a MLS with air bronchogram and multifocal stenosis of RML bronchus in one [7], while the other had a UIP pattern with multifocal narrowing of left upper lobe bronchus [14]. In our study, multifocal bronchial stenosis and peribronchial cuffing were exclusively observed in patients with BAF.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Of the 58 patients with isolated BAF from Iran [17], peribronchial soft tissue thickening, bronchial narrowing or obstruction, segmental atelectasis, and lobar or multilobar collapse were the major findings. The CT findings in the two patients reported from India [7,14] included a MLS with air bronchogram and multifocal stenosis of RML bronchus in one [7], while the other had a UIP pattern with multifocal narrowing of left upper lobe bronchus [14]. In our study, multifocal bronchial stenosis and peribronchial cuffing were exclusively observed in patients with BAF.…”
Section: Discussionmentioning
confidence: 51%
“…Bronchial abnormalities in form of narrowing, multifocal bronchial stenosis, a feature indicative of BAF and peribronchial cuffing were observed. An unusual association of BAF with UIP was observed which was documented in detail [14]. In two studies from Korea www.journals.viamedica.pl [15,16] assessing CT features, bronchial narrowing/ /atelectasis was the most common finding.…”
Section: Discussionmentioning
confidence: 92%
“…Two patients had a UIP pattern, 5 while the third had an NSIP pattern. Both patients were elderly females, never smokers, with a significant history of biomass fuel smoke exposure.…”
Section: Antracofibrosis Bronquial Y Enfermedad Pulmonar Intersticialmentioning
confidence: 98%
“…Only two reports in four patients have been published, 3,4 with only one report detailing the co-occurrence of usual interstitial pneumonia (UIP) pattern with BAF. 5 The rarity of such a description in the literature prompted us to report 2 female patients who underwent diagnostic fiberbronchoscopy (FOB) for evaluation of BAF. A diagnosis of associated ILD was also established in these patients, 1 with non-specific interstitial pneumonia (NSIP) pattern and the other with UIP pattern.…”
Section: Antracofibrosis Bronquial Y Enfermedad Pulmonar Intersticialmentioning
confidence: 99%
“…3 Multifocal narrowing, when present on HRCT, is a characteristic imaging feature of BAF. 3,6 In developed countries, BAF is usually seen in immigrant populations in which elderly women patients would have had long-standing exposure to biomass fuel smoke. In a study from Canada, Hwang et al 7 documented the occurrence of BAF in ten patients from Asia.…”
Section: Clinical Medicinementioning
confidence: 99%